LARVOTHERAPY IN THE TREATMENT OF DIFFICULT-TO-HEAL LESIONS: INTEGRATIVE REVIEW (Estima – Brazilian Journal of Enterostomal Therapy, 2022)
Objective: To analyze the evidence available in the literature about the use of larvotherapy in the treatment of difficult-to-heal wounds. Method: This is an integrative review, having as a guiding question: what evidence is available in the literature about the use of larvotherapy in the treatment of wounds that are difficult to heal? The inclusion criteria were: original articles, literature review and experience reports, from 2016 to 2021, available online in full, in Portuguese, English and Spanish and that answered the research question. Exclusion criteria were: duplicate articles, letters to the editor, dissertations, theses, monographies and research with animals. Searches took place at Virtual Health Library and United Station National Library of Medicine between August and September 2021. Results: Ten articles were selected. The main advantages were: selective debridement, bactericidal or bacteriostatic action, and promotion of granulation tissue and healing factors. The main disadvantages were: pain, discomfort, prejudice, and weaknesses with the larval production market. Conclusion: The advantages found outweigh the disadvantages evidenced. Therefore, larvotherapy is favorable to treat wounds that are difficult to heal.